ChemInform Abstract: New Developments in Direct Functionalization of C—H and N—H Bonds of Purine Bases via Metal Catalyzed Cross‐Coupling Reactions. Issue 30 (July 2015) - Abdoli, Morteza; Mirjafary, Zohreh; Saeidian, Hamid; Kakanejadifard, Ali
Abstract Review: [66 refs.